2005
DOI: 10.1063/1.2001757
|View full text |Cite
|
Sign up to set email alerts
|

Ge diffusion in Ge metal oxide semiconductor with chemical vapor deposition HfO2 dielectric

Abstract: We report a study on Ge diffusion and its impact on the electrical properties of TaN∕HfO2∕Ge metal-oxide-semiconductor (MOS) device. It is found that Ge diffusion depends on the amount of GeO2 formed at the HfO2∕Ge interface and can be retarded by surface nitridation. It is speculated that Ge diffusion is in the form of GeO or Ge-riched HfGeO. Effective suppression of Ge diffusion by NH3 nitridation has resulted in improved electrical properties of TaN∕HfO2∕Ge MOS device, including equivalent oxide thickness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
123
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 11 publications
1
123
0
Order By: Relevance
“…Some literature reported that in situ Ge plasma nitridation for ALD high-k thin film deposition can improve the interface quality [9,18,33]. However, there is rare work on fabrication of the Gebased MOS device with sub-nanometer CET by in situ Ge plasma nitridation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Some literature reported that in situ Ge plasma nitridation for ALD high-k thin film deposition can improve the interface quality [9,18,33]. However, there is rare work on fabrication of the Gebased MOS device with sub-nanometer CET by in situ Ge plasma nitridation.…”
Section: Resultsmentioning
confidence: 98%
“…Nitrogen incorporation into GeO 2 , which causes the formation of GeO x N y , has been used to improve its stability against thermal and wet treatments [16,17]. It was also found that nitridation of Ge surfaces prior to high-k film deposition is effective in suppressing Ge diffusion into high-k film and improving performance of Ge-based devices [18]. The scaled GeO x N y gate dielectrics fabricated by NH 3 plasma pretreatment may be one of the most reasonable solutions for future Ge-MOS devices.…”
Section: Introductionmentioning
confidence: 97%
“…Sequentially, poor interface properties and high gate leakage current will be exhibited in the Ge-MOS device. [3][4][5][6][7] Various pre-gate surface modification techniques, such as surface nitridation or Si passivation, have been developed to improve the quality of gate insulator/Ge interface. 13 It was also reported that high-performance Ge MOSFET could be realized by careful control of interfacial GeO 2 formation.…”
mentioning
confidence: 99%
“…[43][44][45] In Ge/oxide interfaces (for example, Ge/high-k oxide or Ge/GeO x /high-k oxide), there have also been numerous reports that during volatilization germanium out-diffuses into the oxide in the form of Ge atoms or as GeO molecules. 30,[46][47][48][49][50] This could form lattice vacancies or divacancies (V 2 ) in Ge among other possible defects. It is also anticipated that cations from the oxides will diffuse into Ge.…”
Section: Resultsmentioning
confidence: 99%